Effect of Household Processing on the Removal of Pesticide Residues in Okra Vegetable - Sheikh, Saghir A.; Nizamani, Shafi M.; Jamali, Asif A.; Mirani, Beenish N.; Panhwar, Aasia A.; Channa, Mahvish J. (Journal of Basic & Applied Sciences, 2012)
The study has been designed to determine the extent of pesticide residues removal from okra through household processing. For this, okra crop was grown on university farm and application of pesticides were carried out at recommended dosage. After 24 hours, the okra was harvested, labeled and brought to the laboratory of Institute of Food Sciences and Technology, Sindh Agriculture University, Tandojam for their analyses and further processing such as washing, detergent washing, sun-drying and cooking, etc. being practiced at various households. Pesticide residues were extracted from okra by solvent partitioning and cleaned by C18 cartridges/activated charcoal by using acetonitrile for elution and then cleaned up residues were analyzed through HPLC-UV. The analysis of data revealed that imidacloprid is highly effective against pests at low dosages and its residues in processed as well as unprocessed okra samples were within MRLs (0.5ppm). Imidacloprid residues 0.31 ppm in unwashed okra was reduced to 0.082 ppm by detergent washing (73% removal). Emamectin benzoate residues were high in unwashed okra (0.51 ppm as against MRLs of 0.2ppm), however, its residues were reduced to MRLs by detergent washing and subsequent processing by frying, thermal dehydration or sun-drying of detergent washed okra.